Effectiveness of preeclampsia prognosis in pregnancy. - Loskutova, T. O. (Medicni Perspektivi, 2014)
With the purpose to develop and assess the effectiveness of prediction method of pre-eclampsia (PE) 177 women in III trimester of pregnancy were examined. Of them: 133 women with preeclampsia of varying severity, 44 - with uncomplicated pregnancy. Prediction method is based on testing of thrombophilia genes, level of antibodies to β2 glycoprotein-1, D-dimer, value of atherogenicity coefficient. Using maximum likelihood method risk function was designed and formula which allows to estimatie probability of pre-eclampsia development was made. For practical applications, a graphical representation of likelihood of pre-eclampsia development from the calculated risk function is given. The sensitivity of the proposed model is 82,5% (95% CI 74,2-88,9%), specificity – 90,9% (95% CI 78,3-88,9%). To evaluate the effectiveness this prediction method was tested on a group of 108 pregnant women who were tested in the first trimester. 84 pregnant women were in the group with the predicted low risk (P(y)<0,683) and 24 in the group with a predicted high risk (P (y)≥0,683) of pre-eclampsia development. Analyzing the effectiveness of a prediction method it was proved that in the group with predicted high risk of PE absolute risk of preeclampsia increased by 54.7% (95% CI 50,3-59,08), PE of mild severity – by 21,34% (95% CI 16,75-25,92), PE of moderate severity – by 33,33% (95% CI 28,7-37,9), preterm delivery – by 30,86% (95% CI 41,8-50,57), cesarean section in preterm labor and placenta abruption – by 9,5% (95% CI 4,8-14,2 ), fetal distress during labor – by 14,3% (95% CI 9,6-18,97), perinatal losses by 14.2% (95% CI 9,6-18,97), fetal growth retardation – by 42,9% (95% CI 38,3-47,4), the need for neonatal intensive care – by 26,1% (95% CI 21,5-30,6). Practical use of the proposed model allows to identify pregnant women with high risk of pre-eclampsia, to conduct preventive measures, to review plan of prenatal care as for timely hospitalization and to determine fetus state.